The riddle of Malaysian capitalism rent-seekers or real capitalists? - Searle, Peter (Southeast Asia publications series, 1999)
Is capitalism in Southeast Asia "real" or a "chimera"? Is capitalism there sustainable? Malaysia, where a state/business relationship has been forged to create Malay capitalists, presents an illuminating case in the debate. This study identifies this complex interaction as a source of dynamism